Bank erosion process and bank material loss potential in Manahara River, Kathmandu, Nepal - Shrestha, Pramila; Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2008)
The Manahara River, one of the largest tributaries of the Bagmati River has been suffering from bank erosion problem and lateral shifting. Several erosional processes have been observed. Bank erosion causes loss of large amount of sediment from the watershed. The river has been assessed to find out major erosional processes to determine the relative annual sediment displaced from bank and recession rate of bank, the annual riverbank material loss was calculated using data from cross-sectional surveys of two runoff periods one is in 2005 and another is 2006, and using the factors related to bank material, bank vegetation and bank morphology. The major erosional processes identified are rill erosion, gully erosion, sheet erosion, parallel flow erosion and impinging flow erosion and slumping. Absolute bank material loss estimated from cross-sectional survey indicates that percent loss of sediment per cross-section correlates positively with downstream distance. With increase in distance from the origin, sediment gain or loss from transects also increases. The percent gain in downstream portion exceeds percent loss, therefore the river is aggrading. Contrarily, there is no correlation between distance and bank material loss. This indicates that bank material loss at the sites probably depends on local factors (riparian vegetation, bank material, bank morphology and sinuosity) other than the distance of origin of the river. Relative bank material loss assessed at 24 banks undergoing erosion results, 705 m3 sediment depleted annually from banks and mass of displaced material (TDM) is 1243 tons. The total volume and weight of sediment displaced from the Manahara River must be much higher than this value.   doi: 10.3126/bdg.v10i0.1418   Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 33-44